2009
DOI: 10.1038/modpathol.2008.138
|View full text |Cite
|
Sign up to set email alerts
|

Presence of endometrial adenocarcinoma in situ in complex atypical endometrial hyperplasia is associated with increased incidence of endometrial carcinoma in subsequent hysterectomy

Abstract: The distinction of complex atypical endometrial hyperplasia from endometrial adenocarcinoma is often problematic. Foci of back-to-back arrangement of glands or foci of cribriform arrangement of glands smaller than 2.1 mm in diameter are considered insufficient for the diagnosis of endometrial adenocarcinoma by some authors, and sufficient to be diagnosed as endometrial adenocarcinoma by other authors. We refer to these foci as endometrial adenocarcinoma in situ. In this study, we evaluated findings in subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…9,13,32,49 Of the published reports, 10 studies commented on myometrial invasion, and this showed that an average of 44% (241/553; range, 15% to 89%) of concurrent endometrial carcinoma after AEH diagnosis is associated with variable degree of myometrial invasion. 10,13,14 Mittal et al 25 found an association between myoinvasion and the presence of AIS (60%) 20 19/54 (35%) Histologic review Jensen et al 21 18/57 (32%) Histologic review Agostini et al 8 1/17 (6%) AEH is diagnosed on operative hysteroscopy resection products Horn et al 11 58/112 (52%) Histologic review Shutter and Wright 22 24/52 (46%) Histologic review Trimble et al 23 123/289 (43%) Histologic review by a panel Miller et al 24 18/48 (38%) Histologic review Mittal et al 25 13/54 (24%) This figure increased to 66% (22/33) when AEH is associated with carcinoma in situ Histologic review not mentioned Kurman and Norris 6 15/89 (17%) RSS Janicek and Rosenshein 26 19/44 (43%) RSS Widra et al 27 12/24 (50%) RSS Dunton et al 28 12/23 (52%) RSS Ho et al 29 8/29 (28%) RSS Kimura et al 5 9/33 (27%) All women had hysterectomy (another 9 had AEH) Agostini et al 30 7/23 (30%) RSS Bilgin et al 31 11/46 (24%) RSS Merisio et al 32 30/70 (43%) All patients had hysterectomy Karamursel et al 12 35/56 (63%) RSS Garuti et al 33 11/25 (44%) RSS, 11 had AEH Ivanov et al 34 50/100 (50%) RSS Dordevic et al 4 20/72 (28%) RSS Giede et al 13 25/70 (36%) RSS Mittal and Da Costa 35 9/29 (31%) AEH was diagnosed in endometrial polyp Chen et al 9 14/26 (54%) RSS Sub-Burgmann et al 14 298/724 (41%) RSS Hahn et al 10 13 Previous studies have found lack of neither a reliable clinical parameter ...…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…9,13,32,49 Of the published reports, 10 studies commented on myometrial invasion, and this showed that an average of 44% (241/553; range, 15% to 89%) of concurrent endometrial carcinoma after AEH diagnosis is associated with variable degree of myometrial invasion. 10,13,14 Mittal et al 25 found an association between myoinvasion and the presence of AIS (60%) 20 19/54 (35%) Histologic review Jensen et al 21 18/57 (32%) Histologic review Agostini et al 8 1/17 (6%) AEH is diagnosed on operative hysteroscopy resection products Horn et al 11 58/112 (52%) Histologic review Shutter and Wright 22 24/52 (46%) Histologic review Trimble et al 23 123/289 (43%) Histologic review by a panel Miller et al 24 18/48 (38%) Histologic review Mittal et al 25 13/54 (24%) This figure increased to 66% (22/33) when AEH is associated with carcinoma in situ Histologic review not mentioned Kurman and Norris 6 15/89 (17%) RSS Janicek and Rosenshein 26 19/44 (43%) RSS Widra et al 27 12/24 (50%) RSS Dunton et al 28 12/23 (52%) RSS Ho et al 29 8/29 (28%) RSS Kimura et al 5 9/33 (27%) All women had hysterectomy (another 9 had AEH) Agostini et al 30 7/23 (30%) RSS Bilgin et al 31 11/46 (24%) RSS Merisio et al 32 30/70 (43%) All patients had hysterectomy Karamursel et al 12 35/56 (63%) RSS Garuti et al 33 11/25 (44%) RSS, 11 had AEH Ivanov et al 34 50/100 (50%) RSS Dordevic et al 4 20/72 (28%) RSS Giede et al 13 25/70 (36%) RSS Mittal and Da Costa 35 9/29 (31%) AEH was diagnosed in endometrial polyp Chen et al 9 14/26 (54%) RSS Sub-Burgmann et al 14 298/724 (41%) RSS Hahn et al 10 13 Previous studies have found lack of neither a reliable clinical parameter ...…”
Section: Discussionmentioning
confidence: 98%
“…(i) Using different diagnostic criteria for premalignant endometrial lesions such as AEH, AEH with qualifying criteria, such as mild, moderate, severe, or "AEH cannot rule out a more severe lesion", 24 atypical proliferative lesion, 22 endometrial intraepithelial neoplasia, [37][38][39][40] or adenocarcinoma in situ (AIS), 25 Although several studies reported the risk of concurrent malignancy in cases diagnosed with AEH to be around 20% to 25% 2,4-7 and some authors reported these figures as a commonly accepted rate, 13 the overview of published literature demonstrates that this percentage is higher (37%). Although the PPV for malignancy of the local cases in this study is lower than the overall PPV in the published literature (27% compared with 38%), this can be explained by changes in the PPV over time.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences have indicated that patients undergoing hysterectomy secondary to a preoperative diagnosis of AEH will progress to cancer, and the prevalence varies from 20% to 50% [14][15][16][17]. The overall incidence of endometrial cancer on follow-up hysterectomy in the AEH patients reported here was 65.8% (98 patients out of 149).…”
Section: Commentsmentioning
confidence: 84%
“…5 Foci of back-to-back glands or cribriform arrangement of glands in the present case correspond to adenocarcinoma in situ, as proposed by other authors. 9 It is well known that estrogen-related factors play an important role in the development of CAH and endometrial adenocarcinoma. Therefore, a common etiology between APA and CAH may have been involved in the present case, although the two lesions were not linked.…”
Section: Discussionmentioning
confidence: 99%